Media Violence and Quality of Life among Young Children and Youth in Sialkot, Pakistan - Abbas, Salbia; Jami, Rabia; Iddress, Laiba; Abbas, Saira; Bibi, Khuzaifa (Al-Athfal: Jurnal Pendidikan Anak, 2021)
Purpose – Media has proved to be a handy tool in education, arts, science, sports, and culture. People spend most of their time watching television, playing video games, and surfing the internet. This study aims to identify how violence in media affects the quality of life among children and youth.Design/methods/approach – A random sample of 181 individuals ranging in age from 7 to 24 was collected online using a Google form questionnaire. An organized self-report Questionnaire had four segments: 1) Consent Form; 2) Demographic Information of Participant; 3) The Content-based Media Exposure Scale(C-ME); 4) Quality of Life Scale (QOL). First part of C-ME shows that exposure to anti-social media content had a negative relationship with quality of life scale [r= -.189, n= 181, P= .011] while second part of C-ME (neutral items) had a positive relationship with quality of life scale [r= .265, n= 181, P= .00].Findings – Findings of this study suggest that lower quality of life is a genuine and developing phenomenon among young children and youth. Training programs for guidance about media content should be customized to be reasonable for each social setting.Research implications/limitations – Sample size could be increased due to compliance with COVID-19 SOP. Online data were collected via Google forms. More research is required to eradicate this issue among children and youth, turning into aggression later in life. This study welcomes all upcoming researchers to work on this for better results.Practical implications – The results of this study show a positive relationship between media violence and quality of life among young children. The quality of life is highly deteriorating because of anti-social media content in various countries. It shows that lower quality of life is a genuine and developing phenomenon among young children and youth. Training programs for guidance about media content should be customized to eradicate current issues in the community.Originality/value – Results of this study highlight the relationship between media content and the quality of life of young children and youth, but this broad topic still requests conclusive discussion and research worldwide. Paper type Research paper